PENERTIBAN SINDEN PADA PERTUNJUKAN WAYANG GOLEK: KERESAHAN BAGI DALANG DI JAWA BARAT - Masyuning S.Sn., M.Sn. (Paraguna, 2018)
This  paper presented  sind~n as  part of  the  wayang gol~k show  in  West Java. Before the  G30S/PKI incident sind~n was so popular,  it even  beat  the popularity of the   dalang.   This  phenomenon caused  unrest for  the   dalang  in  West Java.   The government intervened  to curb  the  sind~n which was seen as  too wild.  The  incident of sind~n which caused  unrest stopped  after a  seminar padalangan was held  in1964.   This  event proved  that   the  comunity  of Padalangan were able   to  unite to solve that problem.